Healthcare utilisation for eating disorders among patients with depression: a cross-sectional study in Taiwan - Wu-Chien Chien; Chin-Bin Yeh; Chiu-Lan Yan; Li-Ting Kao; Ming-kung Yeh (BMJ Open)
Objectives Although depressed patients may have a comorbid eating disorder (ED), to date, no study has focused on healthcare utilisation among this population. This study was designed to investigate the characteristics of healthcare service utilisation among depressed patients with ED.Design A cross-sectional study.Setting This population-based study used claims data from Taiwan’s National Health Insurance Research database between 2001 and 2012.Participants The study involved 1270 participants. These included 254 depressed individuals with ED and 1016 propensity score-matched depressed individuals without ED.Outcome measures We tracked each patient for a 1 year period to evaluate their healthcare service utilisation, including outpatient visits, inpatient days, and costs for psychiatry and non-psychiatry services. We performed a Mann-Whitney U test to compare outcome variables in healthcare service utilisation between the two groups.Results Patients with both depression and ED had significantly more outpatient visits (32.2 vs 28.9, p=0.023), outpatient costs (US$1089 vs US$877, p<0.001) and total costs (US$1356 vs US$1296, p<0.001) than comparison patients. For psychiatric services, patients with depression and ED had more outpatient visits (11.0 vs 6.8, p<0.001), outpatient costs (US$584 vs US$320, p<0.001) and total costs (US$657 vs US$568, p<0.001) than those without ED. For non-psychiatric services, there was no significant difference for all utilisation. This indicates that the total costs were about 1.0-fold greater for depression patient with ED than those without ED.Conclusion Depression patients with ED had more outpatient visits, outpatient costs and total costs of healthcare services than those without ED.